PENYIMPANGAN PRINSIP KERJA SAMA DALAM PROGRAM TELEVISI WAKTU INDONESIA BERCANDA (WIB) DI NET: KAJIAN PRAGMATIK - Adiella Anggi Bieuty Purbosari; Taufik Nurhadi (Universitas PGRI Adi Buana Surabaya, 2020)
In communication, there is a well-established interaction if there is cooperation between speakers and opponents of speech. In the interaction of language there are interesting events studied from the principle of cooperation. One of them is the language event in the program of Waktu Indonesia Bercanda (WIB). The purpose of this research is to get the result of description about the form of deviation of cooperative principle in TV program Waktu Indonesia Bercanda (WIB). The method used in this research is the method of padan. The data in this study is a speech that contains the deviations of the principle of cooperation on the TV program Waktu Indonesia Bercanda (WIB). Sources of data from this study obtained from TV program Waktu Indonesia Bercanda (WIB) on Net. Techniques of data collection using collect techniques, record and note. The data analysis techniques in this study using descriptive data analysis. The results of the research found in the TV program Waktu Indonesia Bercanda (WIB) there are deviations of the principle of cooperation that includes the four maxims of maxim quantity, maxim quality, maxim relevance and maxim way. Conclusions and suggestions are given so that this study may be of benefit to the reader in particular can be expected to increase knowledge of pragmatic science and its parts including knowledge of deviations from the principle of good cooperation in daily communication.